Identification of novel autoantibody signatures and evaluation of a panel of autoantibodies in breast cancer. Issue 8 (4th July 2021) - Qiu, Cuipeng; Wang, Bofei; Wang, Peng; Wang, Xiao; Ma, Yan; Dai, Liping; Shi, Jianxiang; Wang, Keyan; Sun, Guiying; Ye, Hua; Zhang, Jianying
Abstract: Tumor‐associated autoantibodies (TAAb) could be serological tumor markers. This study aims to discover novel TAAb signatures for breast cancer (BC) detection. The protein microarray was used to identify candidate TAAb, which were further validated in 1197 sera from BC, benign breast diseases (BD), and healthy controls (HC) by enzyme‐linked immunosorbent assay. In addition, 319 preoperative and postoperative sera were evaluated. A panel was determined using four different classifiers. Twelve TAAb were identified with frequencies of 15.8%‐59.2%; their levels were significantly decreased in postoperative sera compared to those in preoperative sera ( P < .05). A panel with six TAAb was developed and evaluated. The area under the curve (AUC) was 0.879 (74.3% sensitivity, 91.9% specificity) and 0.865 (69.7% sensitivity, 91.7% specificity) for distinguishing BC from HC in the training set and test set, respectively. The panel had an AUC of .884 (71.2% sensitivity, 90.5% specificity) for discriminating BC from BD. For identifying BC from all controls (HC+BD), the AUC was .916 (78.9% sensitivity, 90.2% specificity). The AUC of the panel was .920 and .934 for distinguishing stage I‐II and age < 50 BC from HC, respectively. These identified TAAb have the potential to provide a non–invasive approach to detect BC. Abstract : This is the first study using a customized protein microarray consisting of proteins encoded by cancer driver genes to identify novel TAAb as serological biomarkers for BC. In screening 1197 sera samples, we identified 12 TAAb (ALK, BRCA2, CDKN2A, CEBPA, CEP55, FUBP1, GATA3, HIST1H3B, HRAS, PTCH1, p62, and RalA) that are potential biomarkers of BC. The serum levels of 12 TAAb in BC patients had decreased significantly 1 month after the operation. A panel with 6 TAAb (BRCA2, CEBPA, CEP55, FUBP1, HRAS, and RalA) was established. The panel shows superior performance in distinguishing breast cancer from healthy controls or benign breast diseases.